A miríade de atores produtivos na terceirização do calçado em Franca - Almeida, Marina Stefani de (2008)
The aim of this study is to analyze how outsourcing manifests in the Francas footwear industry, interior of São Paulo, and to bring up the consequences of this process for the labor market in this area and for its workers. The research shows that outsourcing has increased segmentation of the labor market in this sector, which was present before, and has fragmented the footwear working class into innumerous atypical forms of work situations, among these the self-employment, domiciliary work, the providers micro-firms and the formal and informal outsourced workers. The outsourcing in Franca calls into question the predominance of the classic industrial work and promotes the dismantling of the workers rights through the flexibilization of the workforce management. The study focuses not only on the technical aspects of outsourcing but, mainly on the experience and subjectivity of the productive actors that experience this process, mentioning the everyday work and the labor relations established in these small productive units. The work uses semi structured interviews, as well as quantitative data about the sector, when they are available.